1972
DOI: 10.1677/joe.0.0550421
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Dynamics in Vitro in the Canine Prostate Gland

Abstract: The uptake and metabolism of androgens by canine prostate in vitro were studied by means of an experimental design which consisted of superfusion of prostate slices with a medium containing [4-14C]androstenedione and [6,7-3H]testosterone, or [4-14C]testosterone and 5\g=a\-dihydro[1,2-3H]testosterone. The entry or transfer of steroids into the slices, the irreversible metabolism, the conversion between the steroids and their uptake or tissue retention were measured at the steady state. A similar proportion of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1974
1974
2010
2010

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…In all the experiments, the steroids had reached steady-state when the determinations used for the calculation of the parameters were made. Since it has been shown that there is no difference in androgen entry or efflux between normal and hyperplastic canine prostate (Giorgi, Stewart, Grant & Reid, 1972), the results obtained in these two types of tissue have been described together.…”
Section: Resultsmentioning
confidence: 99%
“…In all the experiments, the steroids had reached steady-state when the determinations used for the calculation of the parameters were made. Since it has been shown that there is no difference in androgen entry or efflux between normal and hyperplastic canine prostate (Giorgi, Stewart, Grant & Reid, 1972), the results obtained in these two types of tissue have been described together.…”
Section: Resultsmentioning
confidence: 99%
“…The synergistic effects of estrogen on androgenic action may be explained, in part, by increased secretion of prolactin [6], but mostly it seems to be attributable to the direct action of estrogen on the target tissues of androgen [7]. It has been reported that estrogen causes increased permeability of cell membrane [8], interaction with androgen receptor [9], and an increase in DNA synthesis [10]. Together with these various effects, treatment with estrogen increases the weight of prostate and seminal vesicle in castrated testosterone-injected animals.…”
Section: Introductionmentioning
confidence: 99%
“…These 5-alpha-reduced metabolites act as the intra cellular mediators for many of the multiple actions of testosterone [1][2][3][4]. In the prostate, testosterone is also converted into delta-4-androstenedione (delta-4-A), 5-alpha-androstanedione (5-alpha-A) and androsterone (A) [2,[5][6][7][8][9][10][11][12], Benign prostatic hypertrophy (BPH), a common disease in aging men, is frequently associated with increased local 5-alpha-re ductase activity as well as with high tissue concentrations of DHT [13][14][15], The relc-vance of the intraprostatic accumulation of DHT as a possible factor in the development of the disease is underlined by the observa tion that BPH appears exclusively in hu mans and in dogs, i.e. in the only two species in which intraprostatic concentrations of DHT and of the 5-alpha-reductase increase with age [13,14,16].…”
Section: Introductionmentioning
confidence: 99%